Erosion Hazard Level in The Bayang Sani River Basin (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This research is a continuation of previous research on measuring the erodibility of the soil in the Bayang Sani watershed. This research aims to reveal the level of erosion hazard by estimating the volume of soil lost in a field when erosion occurs in the Bayang Sani watershed. This research is quantitative research with a survey method. Data collection techniques were measured in the field and analyzed quantitatively using the Universal Soil Loss Equation (USLE) formula. The results obtained in this study were the level of erosion hazard in the Bayang Sani watershed, namely heavy and very heavy (8.22 – 36.07 tons/ha/year. The weight category on land units V3.III.Ht.Tomp.Lat (8, 22) and very heavy F3.II.Kc.Qal.Lat (33.31 tons/ha/year), V2.II.Kc.Tomp.Lat 36.07 tons/ha/year), V2.II.Sm. Comp. Lat (29.25 tons/ha/year).